Cover Picture: Synthesis, Characterization and Electrochemical Properties of 4, 5‐Diazafluoren‐9‐yl or Fluoren‐9‐yl Terminated Homobimetallic Ruthenium and Osmium Allenylidene, Alkynyl‐Allenylidene Complexes (Chin. J. Chem. 4/2017). Issue 4 (April 2017) - Huang, Jinbo; Zhou, Xiaoxi; Zhao, Qianyi; Li, Shunhua; Xia, Haiping
Abstract : The cover picture shows the structures of rigid dinuclear metallacumulenes with diazafluorene or fluorine fragments. These complexes were derived from 9‐ethynyl‐9‐fluorenol and 9‐hydroxy‐9‐ethynyl‐4, 5‐diazafluorene in the presence of cis ‐OsCl2 (dppm)2 and cis ‐RuCl2 (dppe)2 . Eletrochemical studies have revealed that these complexes display a quasireversible redox behavior and a moderate electronic communication between the two metal centers. Moreover, these new structurally rigid complexes show a remarkably broad absorption in the long‐wavelength region (λmax = 300−700 nm), which would be excellent candidates for optical materials. The bridge in center shows the implied meaning of the rigid structures of these complexes and the electronic communication between the two metal centers. More details are discussed in the article by Xia et al. on page 420–428. Abstract : The cover picture shows the structures of rigid dinuclear metallacumulenes with diazafluorene or fluorine fragments. These complexes were derived from 9‐ethynyl‐9‐fluorenol and 9‐hydroxy‐9‐ethynyl‐4, 5‐diazafluorene in the presence of cis ‐OsCl2 (dppm)2 and cis ‐RuCl2 (dppe)2 . Eletrochemical studies have revealed that these complexes display a quasireversible redox behavior and a moderate electronic communication between the two metal centers. Moreover, these new structurally rigid complexes show a remarkably broad absorption in the long‐wavelength region (λmax = 300−700 nm), which would be excellent candidates for optical materials. The bridge in center shows the implied meaning of the rigid structures of these complexes and the electronic communication between the two metal centers. More details are discussed in the article by Xia et al. on page 420–428.